A stoichiometric perspective of the effect of herbivore dung on ecosystem functioning. Issue 2 (15th December 2017) - Sitters, Judith; Olde Venterink, Harry
Abstract: Ungulate herbivores play a prominent role in maintaining the tree–grass balance in African savannas. Their top‐down role through selective feeding on either trees or grasses is well studied, but their bottom‐up role through deposition of nutrients in dung and urine has been overlooked. Here, we propose a novel concept of savanna ecosystem functioning in which the balance between trees and grasses is maintained through stoichiometric differences in dung of herbivores that feed on them. We describe a framework in which N2 ‐fixing trees and grasses, as well as ungulate browsing and grazing herbivores, occupy opposite positions in an interconnected cycle of processes. The framework makes the testable assumption that the differences in dung N:P ratio among browsers and grazers are large enough to influence competitive interactions between N2 ‐fixing trees and grasses. Other key elements of our concept are supported with field data from a Kenyan savanna. Abstract : We propose a novel concept of savanna ecosystem functioning in which the balance between trees and grasses is maintained through stoichiometric differences in dung of herbivores that feed on them. We describe a conceptual framework in which N2 ‐fixing trees and grasses, as well as ungulate browsing and grazing herbivores, occupy opposite positions in an interconnected cycle of processes. The framework makes the testable assumption that the differences in dung N:P ratio among browsers and grazers are large enough to influence competitive interactions between N2 ‐fixing trees and grasses.